Diverse knowledge for diverse innovation; evidence from Chilean firms - Lauterbach, Rodolfo (Estudios de Economía, 2024)
Using the Chilean Innovation Survey for 2019-2020, this work studies the effects of different knowledge sources on a range of innovation outputs. Findings reveal distinct impacts of sourcing information from competitors, customers, and government agencies on product, process, marketing, organizational, and social innovation outputs. Information from customers has a positive effect on overall innovation. Social innovation is positively influenced by information sourced from government agencies. These findings contribute to the understanding of how different knowledge sources shape innovation outputs on developing countries. They provide valuable insights for firms, policymakers, and researchers seeking to enhance innovation capabilities and inform evidence-based policies.